Demonstration of feedback control using LEGO NXT - Yeo, Kai Xiang. (2012)
Since the beginning of mankind, man has known the use of simple tools in their daily lives. These tools slowly become sophisticated machines as time passes and humans evolved. Invented by humans, machines have been around for hundreds of years. Created by humans, these machines have helped make their lives easier, and make commuting faster.Most of the machines now are driven electronically,where humans only need to press a few buttons and the machine will start working according to the calibrations.Inevitably,these machines have entered the lives of people and will most likely continue to be an important part of their lives.Since the beginning of machines,they are here to “lend a helping hand” to humans. From industries to homes,they help make daily activities less tedious and hazardous.